Attenuation of Humming-Type Noise and Vibration in Vehicle HVAC System Using a Tuneable Dynamic Vibration Absorber - AZIZ, Muhammad Safwan Abdul; MAZLAN, Ahmad Zhafran Ahmad; SATAR, Mohd Hafiz Abdul; PAIMAN, Muhammad Abdul Rahman; GHAPAR, Mohd Zukhairi Abd (Archives of Acoustics, 2022)
Heating, ventilation, air conditioning (HVAC) is one of crucial system in a vehicle. Unfortunately, its performance can be affected by the vibration of HVAC components, which subsequently produced unwanted noises. This paper presents an innovative design solution which called as tuneable dynamic vibration absorber (TDVA) to reduce the humming-type noise and vibration in the HVAC system. A detail investigation is carried by developing a lab-scale HVAC model that has the capability to imitate the real HVAC operation in a vehicle. An alternated air-condition (AC) with a fixed blower speed is implied in the study. The analysis of humming-type noise and vibration induced from the HVAC components are performed, and the TDVA is designed and tuned according to the natural frequency of the AC pipe before the attachment. The humming-type noise and vibration characteristics of the HVAC components are compared before and after the implementation of the TDVA. The findings shown that the HVAC model data compares well with the vehicle data, whereby the implementation of TDVA is found to reduce the vibration of the AC pipe by 79% and 61% in both idle and operating conditions and this subsequently improved the humming-type noise of the HVAC system. It also been observed that the TDVA has an effective frequency range around 75–255 Hz and 100–500 Hz for the HVAC model and vehicle systems, respectively.